Legal Protection of Children's Personal Data in the Digital Era - Devi Novira; Widiah Sri Astuti; Muhammad Fariz Albadi; Harmono Harmono; Mohammad Sigit Gunawan (Journal of Social Research, 2024)
In the rapidly evolving digital era, the use of digital technology has become an integral part of everyday life, including for children. However, this development also raises concerns about the protection of children's personal data in the digital environment, which is vulnerable to misuse and exploitation. The purpose of this study is to determine and analyze the legal protection of children's personal data in Indonesia in the context of the digital era and explore the negative impact of the abuse of children's privacy rights in the digital environment, using a normative juridical research method with a statutory approach. The results show that in Indonesia there are several laws that protect children's personal data, such as the Child Protection Act, the Electronic Information and Transaction Act, the Personal Data Protection Act, the Minister of Communication and Information Technology Regulation, and the Government Regulation on Compensation for Children Who Are Victims of Criminal Acts. The negative impacts of the misuse of children's privacy include the risk of cybercrime, impaired child development, and emotional trauma. Therefore, efforts to improve the protection of children's personal data in the digital era are still needed by the government, technology platform providers, and parents to create a safe online environment that supports children's growth and development. The findings of this study have significant implications for policymakers, legal practitioners, and stakeholders involved in child protection in the digital space. Strengthening the legal framework and ensuring its effective implementation are important steps to protect children's personal data from misuse.